Earlier puberty in boys with type 1 diabetes mellitus compared to a simultaneously recruited group of control adolescents. Issue 2 (8th January 2019) - Gaete, Ximena; Vivanco, Maritza; Lopez, Patricia; Rocha, Ana; Sepúlveda, Carolina; Codner, Ethel
Abstract : Background: Recent studies have suggested that there is an earlier age of onset of puberty in healthy boys. However, no study has determined the age of pubertal development in boys with type 1 diabetes (T1D) and compared the results with a simultaneously recruited group of healthy children. Objective: The aim of this study was to evaluate the age of pubertal events in boys with TD1 and determine whether the duration of diabetes, metabolic control or insulin dose are associated with the age of puberty in boys with T1D. Methods: Boys aged 7 to 19 years with T1D ( n = 148, age 12.9 ± 3.0 years) and healthy boys recruited from schools ( n = 388 controls, age 12.8 ± 2.2 years) were studied. A pediatric endocrinologist evaluated pubertal development. Results: Boys at genital Tanner stage 2 and the final stages of puberty (genital Tanner 4 and 5) were younger than the control group ( P = 0.005, P = 0.003, and P = 0.015, respectively). Both groups of boys had a similar age of pubic Tanner stage development. There were no cases of pubertal delay observed in the T1D cohort. There was no association observed between metabolic control with pubertal timing. T1D adolescents had lower height‐SDS than the C group at the final stages of puberty. Conclusions: Boys with T1D who are treated with modern insulin therapy appear to have an earlier age of onset and an earlier age of final pubertal events than a simultaneously studied group of healthy children. These data suggest that pubertal delay is not a frequent problem for male T1D patients.